2020
DOI: 10.1002/ijfe.2365
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms leading to equilibrium in economy with financial market

Abstract: Joseph Schumpeter pointed to the important role of the economic mechanism, understood as a set of rules and regularities explaining the economic life, within the evolution of the economy. Innovative mechanisms as well as mechanisms of adaptation of innovations into agents' activities were at the core of his interest. This paper aims at designing some kinds of innovative and non-innovative mechanisms that can appear within the economic evolution. Hurwicz mechanisms are used to rigorously study the processes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Some results on mathematical modelling and analyzing of the Hurwicz mechanisms leading to equilibrium in competitive economy can be found in papers by Lipieta (2018), Lipieta and Malawski (2021) as well as Lipieta and Ćwięczek (2020). In Lipieta (2018), it was shown that innovative and imitative processes can coexist in the framework of the same mechanism as well as some preliminary results on mechanisms resulting in the long-run equilibrium were presented.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Some results on mathematical modelling and analyzing of the Hurwicz mechanisms leading to equilibrium in competitive economy can be found in papers by Lipieta (2018), Lipieta and Malawski (2021) as well as Lipieta and Ćwięczek (2020). In Lipieta (2018), it was shown that innovative and imitative processes can coexist in the framework of the same mechanism as well as some preliminary results on mechanisms resulting in the long-run equilibrium were presented.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lipieta and Malawski (2021) analyzed the ecological mechanisms in the results of which at least one harmful commodity or obsolete technology could be excluded from economic processes. Lipieta and Ćwięczek (2020) focused on the exploration of equilibrium mechanisms in economy with financial market.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation